Bioefficacy Studies on Insecticidal Activities of Sargassum wightii with Neem oil against rice Leaf Folder, Cnaphalocrocis medinalis - Balamurugan S.; Kannan, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The experiment was conducted to evaluate the insecticidal activity of solvent extracts of brown algal seaweed, Sargassum wightii and its combination with neem oil against rice leaf folder Cnaphalocrocis medinalis in the Department of Entomology, Faculty of Agriculture, Annamalai University, Tamil Nadu, India during 2022-2023. Seaweed extracts at 6, 7 and 8% concentrations alone and its combination with neem oil @ 0.5 and 1% concentrations were tested against rice leaf folder and compared to neem oil @ 1% as standard check. The combination treatment seaweed extract @ 8% + neem oil @ 1% resulted in the highest larval mortality of 80.00 percent. In seaweed extract @ 8% + neem oil @ 1%, the larva to adult conversion ratio was 1: 0.06 whereas in the untreated control, the ratio was 1:1.